2007
DOI: 10.1073/pnas.0704882104
|View full text |Cite
|
Sign up to set email alerts
|

Self-recognition and self-selection in multicomponent supramolecular coordination networks on surfaces

Abstract: Self-recognition, self-selection, and dynamic self-organization are of fundamental importance for the assembly of all supramolecular systems, but molecular-level information is not generally accessible. We present direct examples of these critical steps by using scanning tunneling microscopy to study mixtures of complementary organic ligands on a copper substrate. The ligands coordinate cooperatively with iron atoms to form well ordered arrays of rectangular multicomponent compartments whose size and shape can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
171
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(178 citation statements)
references
References 32 publications
3
171
2
2
Order By: Relevance
“…[16][17][18][19][20][21][22][23] These frameworks are characterized by a high degree of perfection since their assembly is based on reversible interactions which allow self-selection, -recognition and -correction processes to occur. 22 It has been recently demonstrated that, similarly to their 3D counterparts, 2D MOFs are also stabilized by genuine charge-transfer coordination bonding and that the metallic centers are characterized by well-defined oxidation states. 23 Such systems might be interesting not only as ordered 2D patterns with possible applications in host-guest reactions, nano reactors, etc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22][23] These frameworks are characterized by a high degree of perfection since their assembly is based on reversible interactions which allow self-selection, -recognition and -correction processes to occur. 22 It has been recently demonstrated that, similarly to their 3D counterparts, 2D MOFs are also stabilized by genuine charge-transfer coordination bonding and that the metallic centers are characterized by well-defined oxidation states. 23 Such systems might be interesting not only as ordered 2D patterns with possible applications in host-guest reactions, nano reactors, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, two-dimensional (2D) MOFs could be formed by co-adsorption of d-transition metal atoms such as Fe, Co and Cu. [16][17][18][19][20][21][22][23] Due to its double-ended functionality, when TPA is absorbed in an upright geometry, it can be used for the organic passivation of inorganic surfaces such as Cu(110) 24 and TiO 2 . 25 A perpendicular binding geometry has also been reported for the adsorption of a similar molecule, 2-(trifluoromethyl)-terephthalic acid (C 6 H 3 CF 3 (COOH) 2 ), from solution onto fluorine-terminated Si(111).…”
Section: Introductionmentioning
confidence: 99%
“…327 This dramatic difference can be understood by comparing the different thermodynamic stabilities of the systems and-in particular-the stability induced by the presence of the pyrimidine chelate. While PBP forms a relatively stable coordination network on its own, the phenyl and biphenyl analogues (BPB and BPBP) show only metastable homoleptic coordination on Cu(100).…”
Section: 4'-bis(4-pyridyl)22'-bipyrimidine (Pbp) and Terephthalic Amentioning
confidence: 99%
“…This will allow greater insight into application of these methods for the development and optimization of functional systems. For example, Langner et al 17 studied multipleligand mixtures in controlled ratios that exhibit local self-selection and error correction in a complementary binary metalϪorganic coordination, demonstrating fundamental steps for molecular selforganization using very simple organic species.…”
mentioning
confidence: 99%